Inflammatory Cytokines in Maternal Circulation and Placenta of Chromosomally Abnormal First Trimester Miscarriages. (29th September 2011) - Calleja-Agius, Jean; Jauniaux, Eric; Muttukrishna, Shanthi
Abstract : The impact of abnormal placental karyotype on the inflammatory response within the villous tissue and peripheral circulation of women with miscarriage was evaluated. Villous (n = 38 ) and venous blood samples (n = 26 ) were obtained from women with missed miscarriage. Tissue chromosome analysis indicated 23 abnormal and 15 normal karyotypes. Concentration of tumour necrosis factor alpha (TNFα ), TNF-R1 and TNF-R2, and interleukin (IL)-10 were measured using flowcytometric bead array in fresh villous homogenate, cultured villous extracts, culture medium, maternal whole blood, and plasma. Plasma TNFα /IL-10 ratios were significantly (P < 0.05 ) lower in miscarriages with abnormal karyotype. In the abnormal karyotype group, there were significantly higher levels of TNFα (P < 0.01 ), IL-10 (P < 0.01 ), TNF-R1 (P < 0.001 ), and TNF-R2 (P < 0.001 ) in the villous extracts and culture-conditioned medium compared to normal karyotype group. In miscarriage with abnormal karyotype, there is an exacerbated placental inflammatory response, in contrast to miscarriage of normal karyotype where maternal systemic response is increased.